2016
DOI: 10.5001/omj.2016.68
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HE4, CA-125, Risk of Ovarian Malignancy Algorithm (ROMA) and Risk of Malignancy Index (RMI) in the Preoperative Assessment of Patients with Adnexal Mass

Abstract: HE4 and ROMA showed a very high specificity, but were less sensitive than CA-125 and RMI in premenopausal women. However, they were of comparable sensitivity in postmenopausal women and were valuable in distinguishing benign ovarian tumors or endometriosis from ovarian cancer. Modifying the cut-off values of the different markers resulted in a higher accuracy compared to the standard cut-offs, but at the expense of reduced sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 25 publications
6
36
1
Order By: Relevance
“…The GOT-2 combination model CA125 + HE4 increased specificity from 68% (CA125 alone) to 79% (CA125 + HE4), hereby decreasing the number of false positives. This confirms prior knowledge that the addition of HE4 substantially increase specificity and should be used in the differential diagnosis of women with pelvic tumors [2,14,41,42]. HE4 may be affected by several factors other than cancer [15].…”
Section: Discussionsupporting
confidence: 83%
“…The GOT-2 combination model CA125 + HE4 increased specificity from 68% (CA125 alone) to 79% (CA125 + HE4), hereby decreasing the number of false positives. This confirms prior knowledge that the addition of HE4 substantially increase specificity and should be used in the differential diagnosis of women with pelvic tumors [2,14,41,42]. HE4 may be affected by several factors other than cancer [15].…”
Section: Discussionsupporting
confidence: 83%
“…The gold standard for differential diagnosis of adnexal masses is surgery 4 . Preoperatively, the standard tools for detecting OC are pelvic ultrasonography and measuring serum cancer antigen 125 levels, which could be combined with the menopausal status to calculate the risk malignancy index 5 . However, in daily practice, due to the performance limitations and time consumption of the standard tools, new prognostic assessment methods that are easy to use, inexpensive, and effective are needed for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy of the ROMA score using Abbott ARCHITECT tumour marker assays Nine studies used Abbott ARCHITECT tumour marker assays. [25][26][27][28][29][30][31][32][33] Only one study included all participants in the analysis, regardless of their final histopathological diagnosis (target condition: all malignant tumours including borderline). 32 Two studies excluded women with histopathological diagnoses other than epithelial ovarian cancer, but included women with borderline tumours.…”
Section: Methodological Quality Of Studies Assessing the Roma Scorementioning
confidence: 99%
“…Figure 1 shows the flow of studies through the review process. Fourteen studies reported data on the accuracy of the ROMA score and were included in this article, [25][26][27][28][29][30][31][32][33][34][35][36][37][38] of which nine used Abbott ARCHITECT tumour marker assays [25][26][27][28][29][30][31][32][33] and five used Roche Elecsys tumour marker assays. [34][35][36][37][38] None of the included studies used the Fujirebio Lumipulse G system.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%